Car plate detection system - Siti Nur Aishah Rodziah, Alkhushairi (2012)
Basically, the system using human eyes to detect the car plate and manually compare the plate number through the report file. Sometimes it will take a long time to search. Then this project is developing to make human work easily. The mainly purpose of this system is to monitor and identify vehicles by their license plate. This system can be used in widely applications such as section control, border crossings, entrance security, parking security and road traffic control. The advantage of this system is no need to add any transmitter or special sign on the vehicles because the car plate already have their own identification by referring to their registration car plate number. The image of the driver also can be captured and stored to make this system more secure. The optical character recognition (camera or video) is the main technique in identify every each of the character on the car plate and going through the process of image processing. That means this project is helping and making human easily monitoring the car and captures the image with the new development technology. The result of this system will display through the Graphical User Interface (GUI).